Perspectives : Romantic, Victorian, and Modern literature - Khan, Jalal Uddin (Cambridge Scholars Publishing, 2015)
Perspectives: Romantic, Victorian, and Modern Literature is an up-to-date explication of various popular and classic subjects and authors arranged chronologically. The book, composed of thirteen essays, examines Blake; Coleridge; Byron; Shelley; Keats; Victorian medievalism; the Victorian reaction to British India; (Ben) Jonsonian elements in Yeats; Yeats and Maud Gonne; the treatment of the Irish civil war and Irish nationalism in Yeats; and the treatment of the Spanish civil war in the selected works of modern fiction and nonfiction. Marked by an originality of approach and a freshness and s.